A Discount Approach to Reducing Nursing Alert Burden - Thompson, Sarah A.; Kandaswamy, Swaminathan; Orenstein, Evan (Applied Clinical Informatics, 2024)
Background Numerous programs have arisen to address interruptive clinical decision support (CDS) with the goals of reducing alert burden and alert fatigue. These programs often have standing committees with broad stakeholder representation, significant governance efforts, and substantial analyst hours to achieve reductions in alert burden which can be difficult for hospital systems to replicate.Objective This study aimed to reduce nursing alert burden with a primary nurse informaticist and small support team through a quality-improvement approach focusing on high-volume alerts.Methods Target alerts were identified from the period of January 2022 to April 2022 and four of the highest firing alerts were chosen initially, which accounted for 43% of all interruptive nursing alerts and an estimated 86 hours per month of time across all nurses occupied resolving these alerts per month. Work was done concurrently for each alert with design changes based on the Five Rights of CDS and following a quality-improvement framework. Priority for work was based on operational engagement for design review and approval. Once initial design changes were approved, alerts were taken for in situ usability testing and additional changes were made as needed. Final designs were presented to stakeholders for approval prior to implementation.Results The total number of interruptive nursing alert firings decreased by 58% from preintervention period (1 January 2022–30 June 2022) to postintervention period (July 1, 2022–December 31, 2022). Action taken on alerts increased from 8.1 to 17.3%. The estimated time spent resolving interruptive alerts summed across all nurses in the system decreased from 197 hours/month to 114 hours/month.Conclusion While CDS may improve use of evidence-based practices, implementation without a clear framework for evaluation and monitoring often results in alert burden and fatigue without clear benefits. An alert burden reduction effort spearheaded by a single empowered nurse informaticist efficiently reduced nursing alert burden substantially.
Keywords: clinical decision support; nursing alert burden; alert fatigue; quality improvement; nursing informaticist